Development of a guide for continuous positive airway pressure use - A good fit: Making continuous positive airway pressure work for you. - Meraj, Adeel; Koep, Lauren; Baig, Muhammad R. (Canadian Journal of Respiratory Therapy, 2025)
Background: Obstructive sleep apnea (OSA) is highly prevalent in veterans with mental illnesses such as post-traumatic stress disorder (PTSD). Untreated OSA reduces the effectiveness of the treatment of PTSD. Treatment of OSA has been shown to reduce daytime sleepiness and symptoms of PTSD and depression. Continuous positive airway pressure (CPAP) therapy is the most effective treatment for OSA. A large number of veterans cannot tolerate CPAP therapy due to anxiety and PTSD symptoms. Positive airway pressure (PAP) NAP, a daytime sleep study for patients with anxiety about starting CPAP and exposure-based cognitive behavioural interventions are the mainstay for the management of CPAP intolerance. However, these options are not readily available to veterans in rural areas, who constitute about 40% of veterans registered in the South Texas Veterans Health Care System (STVHCS). Methods: After getting local IRB exemption, we surveyed thirty (30) veterans in the outpatient clinic setting who could not tolerate CPAP therapy to evaluate the need for a tool to improve CPAP adherence. We reviewed the literature and conducted focused group meetings with local and national experts. We also convened consumer groups and stakeholder meetings, including primary care, sleep medicine, and mental health providers. Results: After a comprehensive evaluation process, we compiled a concise self-help guide combining principles of cognitive behavioural therapy using a behavioural hierarchy approach towards CPAP desensitization. This guide can be used by veterans independently at their homes to improve CPAP use. A printer-friendly version is available for download on the South Central Mental Illness, Research, Education and Clinical Center (SC MIRECC) and the South Texas Veterans Healthcare System (STVHCS) website. The guide will be provided to veterans during the initial CPAP setup and available in clinic waiting rooms throughout the system. Conclusion: Our guide will serve as an effective self-help tool to improve CPAP adherence. It may result in the improvement of various medical and psychiatric conditions.